Autonomic Dysfunction Determines Stress-Induced Cardiovascular and Immune Complications in Mice - Batchu, Sri N (J Am Heart Assoc, 2015)
BACKGROUND: Clinical studies suggest that acute inflammation in patients with elevated heart rate (HR) increases morbidity and mortality. The SJL/J (SJL) inbred mouse strain is a unique genetic model that has higher HR and systemic and vascular inflammation compared with C3HeB/FeJ (C3HeB) mice. The goal of this study was to investigate the role of stress on cardiac and vascular complications between 2 strains. METHODS AND RESULTS: Radiotelemetry was used for continuous recordings of HR and blood pressure in mice. Hemodynamic differences between mouse strains were very small without stress; however, tail-cuff training generated mild stress and significantly increased HR (≈2-fold) in SJL compared with C3HeB mice. Circulating proinflammatory monocytes (CD11b(+)Ly6C(H)(i)) significantly increased in SJL mice but not in C3HeB mice after stress. Presence of Ly6C(+) cells in injured carotids was elevated only in SJL mice after stress; however, a transfer of bone marrow cells from SJL/C3HeB to C3HeB/SJL chimeras had no effect on HR or vascular inflammation following stress. Arterial inflammation (VCAM-1(+)) was greater in SJL inbred mice or SJL recipient chimeras, even without stress or injury. HR variability was reduced in SJL mice compared with C3HeB mice. CONCLUSIONS: We found that impaired parasympathetic activity is central for stress-induced elevation of HR and systemic and vascular inflammation; however, immune cells from stress-susceptible mice had no effect on HR or vascular inflammation in stress-protected mice.